2022
DOI: 10.1002/jaoc.12101
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of an online anger management program for justice‐involved youth

Abstract: The authors examined the efficacy of online anger management psychoeducation for justice-involved youth. Results indicated a statistically significant decrease in the adolescent anger rating scale for juveniles who completed the mandated program, prompting consideration of online modalities in postpandemic services. K E Y W O R D S anger, juvenile, mandated, telehealth, virtual Juvenile justice servicesPrior to the COVID-19 pandemic, the juvenile justice efforts in the United States had been shifting away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Overall, the present findings provide renewed support for CBAT efficacy and they add to the growing literature on remotely‐delivered ‘anger management’ programs (e.g., Bjureberg et al, 2022; Braeuer et al, 2022; Mackintosh et al, 2017; Morland et al, 2010). To our knowledge, the present study is also the first reported empirical evaluation of anger treatment outcomes in chronic pain patients.…”
Section: Discussionsupporting
confidence: 76%
“…Overall, the present findings provide renewed support for CBAT efficacy and they add to the growing literature on remotely‐delivered ‘anger management’ programs (e.g., Bjureberg et al, 2022; Braeuer et al, 2022; Mackintosh et al, 2017; Morland et al, 2010). To our knowledge, the present study is also the first reported empirical evaluation of anger treatment outcomes in chronic pain patients.…”
Section: Discussionsupporting
confidence: 76%
“…A few countries have therefore begun to reduce the size of their prison populations by transferring some prisoners to the community due to the high risk of transmissibility in prisons (Rapisarda & Byrne, 2020 ). Additionally, online interventions are replacing traditional face-to-face activities due to the mentioned high transmissibility risks (Braeuer et al, 2022 ; Fromberger et al, 2021 ). Whether the higher dropout rate of online interventions affects the overall effectiveness of the program is unclear.…”
Section: Discussionmentioning
confidence: 99%